Effect of different rates of NPK fertilizer application on growth and yield of several Sabah local tradffional paddy varieties - Grace Flavyeliz Sinong (2017)
ABSTRACT A field experiment was conducted in the net house C of Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Sandakan from May to November 2016. The experiment was carried out to evaluate the effect of NPK fertilizer application (60:30:30, 90:30:60 and 120:30:90} on the growth and yield of several Sabah local traditional paddy varieties (Tadong, Filipin and Seraudah merah variety) in comparison with the high yielding variety (TR8) and to identify if any of the Sabah local traditional paddy varieties shows a positive response to NPK fertilizer. Treatments were arranged as a 4 x 3 factorial using Completely Randomized Design (CRD) with three replications. The collected data was analyzed using two-way ANOVA at 5% significance level. The results revealed interaction of NPK and the different paddy varieties only significant on length of intemodes and dry matter accumulation. Different paddy varieties shows significant difference in most of the parameters, meanwhile, NPK rates only shows significant in culm diameter, internodes length, dry matter, panicle length and 1,00Q-grains weight. The results showed that for vegetative growth related with lodging incidence characteristics, Tadong (Vl} had given the best results of shortest plant height (127.19 cm), culm height (81.66 cm), intemode length (8.11 cm) and a larger culm diameter (0.58 cm) compared with the other local traditional variety. In yield component, Filipin (V2) recorded the most panide numbers (15.66) and percentage of filled grains (80.45%} which in tum having a lower percentage of empty grains (19.54%). Serendah merah (V3) recorded the longest panicle length (24.15 cm) and heaviest weight of 1,000-grains (29.98 g) which in tum produced a higher extrapolated yields (6.00 t ha-1). In terms of NPK rates, 120:30:90 (F3) produced the largest culm diameter (0.51 cm) with shorter intemodes length (8.90 cm), longest panicle length (23.15 cm) and heaviest 1,000 grains weight (24.69 g). From the application of different rates of NPK fertilizer, V2F2 recorded the highest pH of 5.34 which had increase to 1.27 from the initial pH value (4.07) of the Silabukan soil. Higher percentage of total nitrogen (2.55%) was observed on V2F3 where an increment of 0.45% was recorded from the initial total nitrogen (2.10%) of Silabukan soil. V2F3 also recorded the highest soil available phosphorus (0.0181 ppm) which had reduced about 0.086 ppm from the initial phosphorus content (0.105 ppm). Among the Sabah local traditional paddy varieties used in this study, variety that can be suggested to farmers is Serendah merah (V3) treated with 60:30:30 kg ha-1 (Fl) because it may produce a higher yield which was at par with TR8 (HYV). Moreover, the amount of fertilizer used in treatment Fl is the least, thus, it gives an economical advantage as low fertilizer cost is required to achieve high yield and better grain quality. This variety would also be recommended due to their shorter maturity period of 100-110 DAS which may enable farmers to cultivate it twice a year. The second recommendation would be Tadong (Vl} treated with 60:30:30 kg ha-1 (Fl) would be recommended to farmers because it has given the best plant height, culm height, culm diameter and intemode length. This variety given the best results in resistance towards lodging incidence compared with the other local traditional varieties.